Defining Flourishing in Hospitals: A Qualitative Case Study on Maternal-Child Services - Marlinda, Riztie Paramitha Noor; Izzati, Umi Anugerah ; Fachry, Muhammad; Nevangga, Rizky Patria (Universitas Ahmad Dahlan, 2025)
Hospital settings, particularly maternal-child care units, involve high emotional demands that influence employees’ flourishing. This study aimed to examine how hospital employees construct and experience flourishing within such conditions. A qualitative single case study was conducted using semi-structured interviews with three participants representing management, healthcare worker, and non-healthcare worker. Data were analyzed through Reflexive Thematic Analysis following iterative stages of familiarization, inductive coding, and interpretive synthesis. Five themes emerged and aligned with the PERMA framework: positive emotions derived from patient recovery and appreciation; engagement reflected in deep absorption and coordinated teamwork; supportive relationships that buffer emotional strain; meaning rooted in service values and a sense of responsibility; and accomplishment represented by professional growth and pride. These findings indicate that flourishing arises from the interaction of emotional labor, relational support, and personal values embedded in the organizational environment. The study implies that hospitals should strengthen supportive leadership, peer collaboration, reflective spaces, and structured recovery opportunities to sustain engagement, prevent burnout, and cultivate enduring flourishing among employees.